KONSUMSI BUAH DAN SAYUR ANAK USIA SEKOLAH DASAR DI BOGOR - Mohammad, Andika; Madanijah, Siti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2015)
ABSTRACTThe aim of this study was to analyze factors related to fruits and vegetables consumption of elementary school children in Bogor. The design of this study was cross-sectional with purposive sampling. A total of 108 children in SDN Cibanteng 01 in rural area and SDN Papandayan in urban area. Children consumption of fruits and vegetables in SDN Papandayan was higher than SDN Cibanteng. There were significant differences between children consumption of fruits based on ethnic and mother`s job (p<0.05). Children knowledge of nutrition and education of father and mother significantly positive associated with children consumption of fruits and vegetables, as well as pocket money, availability of fruits in house, and family income positive significantly associated with children consumption of fruits (p<0.05).Keywords: children, consumption, fruits and vegetables, socio-economicABSTRAKTujuan penelitian ini adalah menganalisis faktor-faktor yang berhubungan dengan konsumsi buah dan sayur pada anak usia sekolah dasar di Bogor. Desain penelitian ini adalah cross sectional dengan teknik penarikan subjek secara purposive sebanyak 108 subjek di dua sekolah dasar di Bogor yaitu SDN Cibanteng 01 Kabupaten Bogor dan SDN Papandayan Kota Bogor. Konsumsi buah dan sayur di SDN Papandayan lebih besar dibandingkan dengan SDN Cibanteng. Terdapat perbedaan yang nyata konsumsi buah anak berdasarkan suku dan pekerjaan ibu (p<0,05). Pengetahuan gizi anak dan pendidikan ayah dan ibu berhubungan signifikan positif dengan konsumsi buah dan sayur anak, demikian pula uang saku, ketersediaan buah, dan pendapatan keluarga berhubungan signifikan positif dengan konsumsi buah anak (p<0,05).Kata kunci: anak, buah dan sayur, konsumsi, sosial-ekonomi